A Coin Hoard of Pre-Reform Shillings of the Grand Master Michael Küchmeister von Sternberg Found in Chernihivschyna - Orlyk, Vasyl (Acta Archaeologica Lodziensia, 2021)
In the 14th and 15th centuries the trading contacts of Volhynia and Podolia with the Teutonic Order ran through the city of Toruń, which was perfectly natural. Those contacts had an influence on the circulation of coinage in the two territories named above, which is attested to by the presence of coins of the Teutonic Order. In September 2014 in the Nizhinsky region, Tschernikhov oblast, was found a hoard in which were coins struck by the Grand Master Michael Kuhmeistra von Sternberg and a half-groschen of Władysław Jagiełło. The coins of the Order, which are described in this article, passed through the hands of the author.